Is it possible to overcome disgust? An ambivalent emotion (Lebenswelt. Aesthetics and philosophy of experience., 2020)
A growing interest for the emotion of disgust has recently arisen in international contexts acrossseveral fields of research. A general definition of disgust will be primarily assumed: by disgust I understand a total rejection that generates a motion of repulsion and removal of an object that is in the proximity of the subject, without constituting a real danger. In reference to the notion of taboo, I will first of all assume its ambivalence. The emotion of disgust, essentially natural and cultural at the same time, as a typical trait of the process of human civilization that distinguishes humans from animals. At variance with other theories of disgust, I will argue that it is not possible to theoretically articulate the overcoming of disgust, but that it is possible to educate about this emotion through artistic experience. On this ground, an ethics of disgust will be outlined, which starts from the acknowledgement of one of our most bodily emotions.